'The Older I Get, the Colder I Get'—Older People's Perspectives on Coping in Cold Homes. Issue 4 (2nd October 2019) - Hughes, Caroline; Natarajan, Sukumar
Abstract: An average of 26, 560 UK excess winter deaths occur in people 65+ years old each winter, of which 30% are attributed to cold homes. Cold homes are known to exacerbate health problems prevalent in the 65+ demographic. Through conducting interviews in homes occupied by 65+-year-olds known to be achieving less than the World Health Organization (WHO) minimum recommended temperature (18ºC), this article highlights their struggles in maintaining health and managing their homes, with instances of extreme and potentially dangerous methods to achieve thermal comfort identified. Fairer energy provision, better targeted financial aid, and improved support networks are necessary to alleviate current problems.